Saponins in Lonicera-Derived Medicinal Materials: A Review of Phytochemistry, Biological Activities, and Implications for Quality Control - Thi Diem Hong, Le; Nam Nhat, Hoang (VNU Journal of Science: Medical and Pharmaceutical Sciences; Acticle in Press, 2026)
Lonicera -derived medicinal materials are a group of crude drugs obtained from species of the genus Lonicera , currently recognized mainly in two medicinal forms: honeysuckle flower and honeysuckle stem. Honeysuckle flower consists of dried flower buds with some opened flowers, whereas honeysuckle stem refers to the stems or leafy branches. This review summarizes and compares data on saponins from four species, namely Lonicera japonica , Lonicera dasystyla , Lonicera confusa , and Lonicera cambodiana , with a focus on phytochemical characteristics, structural features, biological activities, and relevance to quality control. The available evidence shows an uneven distribution among these species. L. japonica is the most extensively studied species, with data on compound isolation, structural elucidation, and bioactivity evaluation at the level of purified compounds. L. confusa is mainly discussed in relation to quality control and authentication of botanical origin, whereas data on L. dasystyla and L. cambodiana remain limited. Overall, saponins may serve as auxiliary markers for chemotaxonomy, botanical authentication, and quality control of Lonicera -derived medicinal materials.